Study of Application of Standard Operating Procedure Grooming at Grand Hotel Preanger Bandung - Nisa Rahmaniyah Utami; Roels Ni Made Sri Puspa Dewi (Media Pendidikan Gizi dan Kuliner, 2022)
Standard grooming procedures are the main requirements that must be known by a kitchen cook so that they can create food that is suitable for consumption and avoids bacteria. In this paper, the purpose of this research is to determine the application of standard operating procedure grooming at the Grand Hotel Preanger Bandung, to determine the effect of applying standard grooming in the kitchen. The method of taking numbers is done by using a questionnaire for 5 employees. The data was collected by using the field method which consisted of observation and questionnaires. The analytical technique used in this study is a quantitative technique. The conclusion of this study is that the application of standard grooming procedures at the Grand Hotel Preanger Bandung obtains data from the results of research written.